Promoting Millet Consumption Through Community-Based Awareness in Northern Sri Lanka: A Case Study of The Nallur Divisional Secretariat Division, Jaffna District - Menaka, S. (University of Colombo Institute for Agro-Technology and Rural Sciences, Sri Lanka, 2025)
Millets have been vital to Sri Lanka’s rural agriculture. However, their cultivation and consumption have declined. This study was conducted in four Grama Niladhari divisions of the Nallur Divisional Secretariat, Jaffna District. One hundred households were selected by systematical sampling method and forty school children were involved in millet cookery sessions along with one of their parents. Data on socio-demographics, millet knowledge, consumption frequency and barriers to millet usage were collected through interviews. Awareness exhibitions, millet seed displays, nutritional education and recipe booklets were used to promote millet usage. When provided with finger millet (Eleusine coracana), little millet (Panicum sumatrense), foxtail millet (Setaria italica), pearl millet (Pennisetum glaucum) and kodo millet (Paspalum scrobiculatum), over 90% of participants were able to identify finger millet across all divisions. However, identification of the other millet types remained below 30%. Use of finger millets in home cooking was reported by 61% of the participants, although typically only twice monthly or less. Consumption of other millets were reported below 12%. This was due to market scarcity, higher costs and insufficient local milling facilities. Farmers also cited poor market access and low demand as key challenges. During cookery sessions, participants prepared innovative dishes like rainbow pittu, drumstick-leaf rotti, and millet-based porridges. A follow-up survey revealed that household millet consumption increased from 12% to 42% after the intervention. Engagement of school children and family members facilitated knowledge transfer and cultural preservation. To support farmers, authorities should establish dedicated market infrastructure. The study highlights the potential of participatory programs to restore traditional food practices, support sustainable agriculture and improve community nutrition.
Keywords: Community engagement; Millets; Participatory research; Sustainable nutrition; Traditional foods